Analisis Efektivitas Teman PBB Kota Bandung Sebagai Inovasi Digital untuk Optimalisasi Penerimaan Pajak Bumi dan Bangunan - Dian Novita Ramadani; Restu A Suryaman; Gugum Mukdas Sudarjah (JRAK: Journal of Accounting Research and Computerized Accounting, 2026)
This study aims to evaluate the implementation of the Teman PBB application in Bandung City as a digital innovation designed to improve local tax compliance. The background of this research stems from the low level of tax compliance at the local level and the need to modernize tax administration through digital services. This study employs a qualitative descriptive approach supported by simple quantitative data collected through a survey of 100 taxpayers, complemented by participatory observation at the UPTD PPD Central Bandung Region. The results show that low digital literacy and limited public awareness are the main barriers to application adoption, as reflected by only 11% of respondents being aware of the existence of Teman PBB. In addition, technical issues such as server limitations, non-user-friendly interfaces, and system instability reduce the perceived usefulness and ease of use, as explained in the Technology Acceptance Model. From a policy perspective, the application has not yet been able to fully build public trust, as described in the Slippery Slope Framework. This study concludes that the success of Teman PBB is strongly determined by improvements in digital literacy, enhancement of technical quality, and cross-sector collaboration, including integration with digital payment platforms to strengthen voluntary compliance and the effectiveness of local fiscal revenue.